ANALYSIS OF RATING SCALE MENTAL EFFORT (RSME) TO DETERMINE THE MENTAL WORKLOAD OF WORKERS AT SUGAR FACTORY IN SOUTH SULAWESI - Rahmaniah Malik; Irma Nur Afiah; Muhammad Dahlan; Zakir Sabara HW; Taufik Nur; Risal Iswandi (Universitas Mercu Buana, 2021)
Unconducive working conditions triggered fatigue and anxiety for the workers, such as an increase in mental workload. Mental workload is a work load that arises and can be seen from the work that has been carried out, which is formed cognitively (mind). Generally, mental workload is the difference between mental work demands and mental abilities possessed by the worker concerned. The level of workload of workers can be determined by applying workload analysis. One of the mental workload analysis methods is the Rating Scale Mental Effort (RSME) which is a method of mental workload measurement. The aims of this research are to determine the level of mental workload of workers, to identify the main causes of mental workload in the sugar production division, and also to provide suggestions to the company on the basis of identifying the mental workloads. The results of the study using workload analysis showed that the mental workload was quite high, i.e., the morning shift reached 97.3, the afternoon shift reached 101.8 and the night shift reached 99.66. The mental workload occurred due to continuous activities such as the sugar production process and excessively hot environment, as well as too high company targets.